PEMETAAN DAERAH RAWAN KEBAKARAN HUTAN DAN LAHAN DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (STUDI KASUS KECAMATAN BUKIT BATU, KABUPATEN BENGKALIS) - Ajriansyah Putra; Ambar Tri Ratna Ningsih; Muhammad Ikhwan (Fakultas Pertanian, Universitas Riau, 2018)
This study aimed to map the level of vulnerability of forest and land fires in an effort to supportthe realization of forest fire prevention strategies in Bengkalis Regency area by consideringaspects of land cover, soil type, rainfall, altitude and distance of settlement. This research wasconducted in Bukit Batu District, Bengkalis. This study uses a survey method in collectingsecondary data and primary data. Data analysis was conducted by classifying each observationparameter. The results of this study indicate that the level of vulnerability of fires in District ofBukit Batu is divided into two classes, which are very high and prone to high vulnerability.Most of the sub-districts of Bukit Batu have very high vulnerability. The high vulnerability areahas an area of 27,533,611 ha (22.49%) and very high of 94,915.83 (77.51%). Determinants thatplay a major role in influencing the high level of vulnerability in a location are land cover,rainfall, and soil type.